The Challenge of Pancasila in the Development of the Millennial Generation - Aimana, Salwa Nadiyah (Universitas Negeri Semarang, 2017)
The Indonesian nation has a unifying tool for the nation which is formed from the noble values of Indonesia. In the era of the Majapahit kingdom, in the book Sutasoma by Mpu Tantular it is written